Atypical Leiomyoma: a rare histologic variant - A Diagnostic Challenge - Pujani, Mukta; Hassan, Mohammad Jaseem; Rana, Safia; Jetley, Sujata (Bangladesh Journal of Medical Science, 2018)
Bizarre or atypical leiomyoma (LM) is defined as “leiomyoma containing giant cells with pleomorphic nuclei and little or no mitotic activity.” Due to the ominous and worrisome microscopic appearance (many large giant cells with hyperchromatic, pleomorphic, malignant looking nuclei), this variant maybe misdiagnosed as a sarcoma. It, therefore presents a diagnostic challenge to the pathologist to accurately diagnose such a tumor while ensuring that a true malignancy is not overlooked. We report a case of a atypical leiomyoma of the uterus in a 40 year old female presenting with irregular menstrual bleeding. This highlights the need for extensive tissue sampling in such dubious cases to help arrive at a correct diagnosis. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.511-514